CHANGE OF BUSINESS ENTITY TO THE EXISTENCE OF BUSINESS LICENSE IN REALIZING LEGAL GUARANTEE AND EASY BUSINESS IN INDONESIA. - Teuku Ahmad Yani; Azhari Yahya; Abdurrahman Abdurrahman (Kanun Jurnal Ilmu Hukum, 2022)
The laws and regulations in Indonesia recognize various legal forms of companies; however, the legal form of a Limited Liability Company is considered to have better business prospects. Limited Liability Company also becomes a legal form of a company that can conduct business in all business fields. This condition has led to the practice of changing the legal form of companies in Indonesia from companies with certain legal forms to the legal form of Limited Liability Companies. This change in the legal form of the company is not covered by a special law that can combine the needs of changing the legal form of the company. In practice, this change in legal form is carried out in various ways that may result in legal uncertainty on one hand, and licensing difficulties as a result of a change in legal form on the other hand. Therefore, a new concept that can create legal certainty and ease doing of business in changing the legal form of companies in Indonesia is needed.